2020
DOI: 10.1136/bmjopen-2019-035888
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Life Centres: a 3-month behaviour change programme’s impact on participants’ physical activity levels, aerobic fitness and obesity: an observational study

Abstract: ObjectivesIndividuals with low socioeconomic status and multimorbidity tend to have lower physical activity (PA) levels than the general population. Primary care is an important setting for reaching high-risk individuals to support behaviour change. This study aimed to investigate the impact of behaviour change interventions delivered by Norwegian Healthy Life Centres (HLCs) on participants’ PA levels, aerobic fitness and obesity, and furthermore to investigate possible predictors of change.DesignAn observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Most of the included studies lasted ≥ 6 months, and overall, there was an improvement over time in SBP, DBP, and HR. A probable explanation for the difference between the findings from this review to those from the present research is that longer interventions promote better results in terms of physiological changes [ 85 , 86 , 87 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Most of the included studies lasted ≥ 6 months, and overall, there was an improvement over time in SBP, DBP, and HR. A probable explanation for the difference between the findings from this review to those from the present research is that longer interventions promote better results in terms of physiological changes [ 85 , 86 , 87 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Similar to the INT group, aerobic fitness tended to increase in the CTRL group, which can be potentially explained by the increase in LIPA after 12 weeks (all days and weekend days). Indeed, Blom et al 41 observed that interventions aiming to increase LIPA improve aerobic fitness in obese adults. It has been reported that habitual LIPA is a great indicator of better strength performance on the lower limb 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Participants’ level of education (high versus low) could not explain PA improvements in a 3-month observation study encompassing greater numbers of participants from multiple HLCs [ 21 ]. The same study revealed that not only did participants with mental or somatic diseases and with excess weight improve their PA level, the same was true of their peers.…”
Section: Mitigating Social Health Disparitiesmentioning
confidence: 99%